Being the victim of virtual abuse changes default mode network responses to emotional expressions. (February 2021) - Seinfeld, Sofia; Zhan, Minye; Poyo-Solanas, Marta; Barsuola, Giulia; Vaessen, Maarten; Slater, Mel; Sanchez-Vives, Maria V.; de Gelder, Beatrice
Abstract: Recent behavioural studies have provided evidence that virtual reality (VR) experiences have an impact on socio-affective processes, and a number of findings now underscore the potential of VR for therapeutic interventions. An interesting recent result is that when male offenders experience a violent situation as a female victim of domestic violence in VR, their sensitivity for recognition of fearful facial expressions improves. A timely question now concerns the underlying brain mechanisms of these behavioural effects as these are still largely unknown. The current study used fMRI to measure the impact of a VR intervention in which participants experienced a violent aggression from the specific vantage point of the victim. We compared brain processes related to facial and bodily emotion perception before and after the VR experience. Our results show that the virtual abuse experience led to an enhancement of Default Mode Network (DMN) activity, specifically associated with changes in the processing of ambiguous emotional stimuli. In contrast, DMN activity was decreased when observing fully fearful expressions. Finally, we observed increased variability in brain activity for male versus female facial expressions. Taken together, these results suggest that the first-person perspective of a virtual violent situation impacts emotion recognition through modifications in DMN activity. Our study contributes to a better understanding of the brain mechanisms associated with the behavioural effects of VR interventions in the context of a violent confrontation with the male participant embodied as a female victim. Furthermore, this research also consolidates the use of VR embodied perspective-taking interventions for addressing socio-affective impairments.